2020
DOI: 10.1186/s13019-020-1056-y
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative routines and surgical techniques for saphenous vein harvesting in CABG surgery: a national cross-sectional study in Sweden

Abstract: Background: The saphenous vein is the most commonly used conduit for coronary artery bypass grafting (CABG). Wound healing complications related to saphenous vein harvesting are common, with reported surgical site infection rates ranging from 2 to 20%. Patients' risk factors, perioperative hygiene routines, and surgical technique play important roles in wound complications. Here we describe the perioperative routines and surgical methods of Swedish operating theatre (OT) nurses and cardiac surgeons. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…An earlier study including national data from all cardiothoracic surgery centres in Sweden indicated that local traditions may be among the most important factors determining which procedures are employed in the operating theatre [34]. Such traditions would likely affect the external factors (operation time, type of sutures, vein harvesting technique, suturing experience, etc.)…”
Section: Limitationsmentioning
confidence: 99%
“…An earlier study including national data from all cardiothoracic surgery centres in Sweden indicated that local traditions may be among the most important factors determining which procedures are employed in the operating theatre [34]. Such traditions would likely affect the external factors (operation time, type of sutures, vein harvesting technique, suturing experience, etc.)…”
Section: Limitationsmentioning
confidence: 99%